2007
DOI: 10.1128/jcm.01735-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of Enzyme-Linked Immunosorbent Assay and Dipstick Assay for Detection of Strongyloides stercoralis Infection in Humans

Abstract: The sensitivities of the assays were evaluated using sera from 90 patients with parasitologically proven intestinal strongyloidiasis and from 9 patients with clinical larva currens. The sensitivities of the AMC-ELISA, dipstick assay, IVD-ELISA, and Bordier-ELISA were 93, 91, 89, and 83%, respectively, for intestinal strongyloidiasis. In all tests, eight of nine sera from patients with larva currens were positive. The specificity was assessed using a large serum bank of 220 sera from patients with various paras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
94
2
16

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 25 publications
(25 reference statements)
3
94
2
16
Order By: Relevance
“…According to the high prevalence of strongyloidiasis in the rehabilitation care center, the true prevalence would be higher if specific diagnostic methods such as Baermann technique and agar plate culture method were used [11,32,33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the high prevalence of strongyloidiasis in the rehabilitation care center, the true prevalence would be higher if specific diagnostic methods such as Baermann technique and agar plate culture method were used [11,32,33] .…”
Section: Discussionmentioning
confidence: 99%
“…Serological methods can reveal light infections in asymptomatic individuals and should be used for further studies among those population [11,15,32] and in order to achieve real prevalence, screening procedures must be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Serological methods have higher sensitivity in a chronically infected population [5]. Enzyme-linked immunosorbent assay (ELISA) to detect human immunoglobulin G (IgG) against a crude extract of infective larvae is one of the most widely used techniques for the diagnosis of strongyloidiasis, with sensitivity rates between 73% and 100% [6].…”
mentioning
confidence: 99%
“…This strongly suggests that these patients have infection with Strongyloides or another cross-reacting helminth, rather than past infection. Regarding cross-reactivity, the test used has been shown to have specificity of over 95%, with significant cross-reactivity reported only to filaria [6], which has very limited occurrence in Vietnam [11]. Other studies have shown lower specificity [12], and the manufacturers own datasheet suggests a specificity of 77% in patients with other helminth infections [13].…”
mentioning
confidence: 99%
“…Serology by ELISA can also be used to diagnose S. stercoralis. 6 In a study of sera from 164 hematological patients tested for the presence of Ab to S. stercoralis, the Ab was detected in serum using ELISA. The sensitivity, specificity, and positive and negative predictive values were 68, 89, 48 and 95%, respectively.…”
mentioning
confidence: 99%